A Global Curvature Pinching Result of the First Eigenvalue of the Laplacian on Riemannian Manifolds. (28th March 2013) - Wang, Peihe; Li, Ying
Abstract : The paper starts with a discussion involving the Sobolev constant on geodesic balls and then follows with a derivation of a lower bound for the first eigenvalue of the Laplacian on manifolds with small negative curvature. The derivation involves Moser iteration.